2014
DOI: 10.15835/nsb639331
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Distribution of Vascular Epiphytes in Different Areas in Obafemi Awolowo, Nigeria

Abstract: Composition and distribution of vascular epiphytes were studied in three different areas at Obafemi Awolowo University estate, Nigeria. Each plot, in the selected area, was used for identification of host and epiphytes. Trees were carefully examined. Presence, positions on the host plants and life-forms of all the epiphytes were recorded. Diameter at breast height of the hosts, bark characteristics and height were determined. The climatic data of the areas were measured to determine the relationship between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The dominant nature of the terrestrial ferns could also be an indicator to the lesser degree of disturbance of the forests in the two countries when considered on a larger scale. Researchers have confirmed the dominant nature of terrestrial ferns in less-disturbed forests (Keerthi et al, 2001;Oloyede et al, 2014;Rahmad & Akomolafe, 2018;Sathapattayanon & Boonkerd, 2006). The nonmetric multidimensional scaling analysis showed that the Malaysian and Nigerian forests are more associated with terrestrial and epiphytic ferns than the other life forms of ferns (Figure 4).…”
Section: Patterns Of Life Forms Of Ferns Between the Two Countriesmentioning
confidence: 92%
See 1 more Smart Citation
“…The dominant nature of the terrestrial ferns could also be an indicator to the lesser degree of disturbance of the forests in the two countries when considered on a larger scale. Researchers have confirmed the dominant nature of terrestrial ferns in less-disturbed forests (Keerthi et al, 2001;Oloyede et al, 2014;Rahmad & Akomolafe, 2018;Sathapattayanon & Boonkerd, 2006). The nonmetric multidimensional scaling analysis showed that the Malaysian and Nigerian forests are more associated with terrestrial and epiphytic ferns than the other life forms of ferns (Figure 4).…”
Section: Patterns Of Life Forms Of Ferns Between the Two Countriesmentioning
confidence: 92%
“…In Nigeria, the fern species were collected from the campus of the Obafemi Awolowo University (OAU), Ile‐Ife, Osun State and the reserved forest near Ikogosi warm spring, Ekiti State (Figure 1 ). This University campus is located in Ile‐Ife which lies between latitude 7°32′N, longitude 4°32′E and elevation 258 m. The campus was originally sited on a primary forest which has now been transformed into secondary forest due to the level of human encroachments (Oloyede et al, 2014 ). Ile‐Ife city falls within the tropical rain forest zone of Nigeria which receives an average annual rainfall of 1400 to 1500 mm and a mean annual temperature ranging between 27°C and 34°C.…”
Section: Methodsmentioning
confidence: 99%